Analisis Penyebab Cacat Produk Menggunakan Metode Failure Mode And Effect Analysis (FMEA) Pada PT. Sinar Sanata Electronic Industry - Ardyansyah, Risky; Haniza, Haniza; Sutrisno, Sutrisno (INCODING: Journal of Informatics and Computer Science Engineering, 2024)
The old machine condition can give losses in the company, where the machines can not work optimally which commonly causes the defective product as much as 12%. The defect percentage has been over the tolerance limit of the company, which is only 6-9%. This study aims to analyze the worst defect level by finding out the highest damage value of the Risk Priority Number (RPN). The analysis of the failure mode occurred was conducted through Failure Mode and Effect Analysis (FMEA) Method by concerning to the defect level of the high value of Occurrence, Severity, and Detection that generated the highest damage value. The highest analysis value based on this method was the RPN value that exceeded the critical value which was 100 RPN. Then to solve the problem, the analysis results utilized the Fault Tree Analysis (FTA) method to find out the cause of the failure mode. After that, the Fishbone diagram method was used to determine the cause and effect (Cause-Effect) that cause product defects to occur. Furthermore, the results showed that the value had exceeded the critical number, where 180 RPN were obtained in crack mode and 240 RPN in asymmetric diameter mode. Then the highest critical value was obtained in the crack mode and asymmetrical diameter as the biggest factor of the product defects occurred. Therefore the results of this study are expected to reduce the  high  level of  product defects occur, by evaluating and re-concerning the production  process periodically on noticing the two biggest factors that greatly affect the occurrence of product defects in the company